EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS DIGITAL DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR : STUDI LITERATURE REVIEW - Rahma Putri, Desti; Apri Hamdani, Muhammad; Ilman Nafiah, Zidni; Suriani, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study aimed to determine the effectiveness of digital-based learning media in elementary school mathematics learning. This is because students are not particularly interested in abstract mathematical concepts. Various sources, including books and scientific journals, were reviewed to examine this. The analysis showed that the use of digital-based learning media, including visual, audio, and visual media, improves students' understanding of concepts, boosts their motivation to learn, and improves their learning outcomes. Students can visualize abstract concepts more concretely and more easily understood using digital-based learning media. Therefore, this media is considered effective and should be optimized in elementary school mathematics learning.